Peran Financial Technology dalam Meningkatkan Efisiensi dan Minimalisasi Risiko Operasional: Studi Kasus pada Koperasi Karyawan (Kopkar) PLN Sumedang - Rima Elya Dasuki; Agus Muhammad Ramdani (J-Coop : Journal of Co-operative, 2025)
Kopkar PLN-Sumedang manages various business units, such as savings and loans, waserda, workshops, and others, as well as implementing e-payment financial technology (fintech) applications to serve the needs of its members. However, this cooperative management information system is still less than optimal in providing the information needed by members. The implementation of fintech e-payment is expected to improve the quality of cooperative services, both in business and other activities. This research uses quantitative methods, namely case studies, through questionnaires, observations and literature studies. The research object is the Sumedang Employees Cooperative, with respondents in the form of members, administrators, supervisors, managers and cooperative employees. The research results show that fintech infrastructure meets good criteria to support cooperative business activities. However, the quality of the cooperative management information system is still less than optimal, especially in terms of service and delivery of information to members. The application of fintech is expected to improve management information systems and provide direct benefits for members.